2014
DOI: 10.14712/18059694.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effect of Epigallocatechin Gallate Against D-Galactosamine-Induced Injury in Primary Culture of Rat Hepatocytes

Abstract: Literature data support that green tea and its major component epigallocatechin gallate (EGCG) have powerful antioxidant effects. Contrary, hepatotoxicity can be induced by high-dose EGCG. The timing of exposure to green tea in relation to administration of hepatotoxic agent plays an import role too. The aim of our work was a verification of antioxidative effect of EGCG on D-galactosamine-induced injury in primary culture of rat hepatocytes. Hepatocytes were incubated with EGCG at concentrations of 1.25-10 μM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Hepatotoxin, GalN is mainly concerns either with insufficiency of uridine diphosphate (UDP)-glucose or UDP-galactose that leads to inhibition of energy metabolism on hepatocytes or damaging mitochondrial membrane to release cytochrome C from hepatocytes through oxidative stress. [ 42 43 ] These changes resulted in leakage of aminotransferases and alkaline phosphatase enzymes from hepatocytes into serum and considers as sensitive indicators for hepatic injuries. The rises of AST, ALT and alkaline phosphatase in serum are significantly attenuates during BR treatments suggests its stabilizing/protecting role on hepatocyte cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxin, GalN is mainly concerns either with insufficiency of uridine diphosphate (UDP)-glucose or UDP-galactose that leads to inhibition of energy metabolism on hepatocytes or damaging mitochondrial membrane to release cytochrome C from hepatocytes through oxidative stress. [ 42 43 ] These changes resulted in leakage of aminotransferases and alkaline phosphatase enzymes from hepatocytes into serum and considers as sensitive indicators for hepatic injuries. The rises of AST, ALT and alkaline phosphatase in serum are significantly attenuates during BR treatments suggests its stabilizing/protecting role on hepatocyte cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) is the most abundant and potent catechin of green tea [ 1 ]. Its cytoprotective effect was reported in the liver [ 2 4 ] and other organs, for example, kidney [ 5 , 6 ], heart [ 7 , 8 ], and lungs [ 9 ]. The protection is mediated partly by its direct antioxidant effect [ 10 12 ] and partly by the induction of Nrf2-dependent gene expression [ 5 , 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Galloylated catechins have stronger health effects as compared to the non-galloylated catechins, with respect to the product quality in tea processing and pharmacological efficacy in humans ( Bigelow and Cardelli, 2006 ; Tsutsumi et al, 2011 ). Galloylated catechins possess antioxidant, antibacterial, and anti-inflammatory effects and alleviate cardiovascular diseases ( Braicu et al, 2011 ; Jin et al, 2013 ; Kim et al, 2013a ; Moravcova et al, 2014 ); however, their subcellular localization have not been fully addressed ( Suzuki et al, 2003 ; Liu et al, 2009 , 2012 ). Previous studies have demonstrated that catechins were mainly located in the chloroplasts or vacuoles at the subcellular level ( Suzuki et al, 2003 ; Liu et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%